(3GdNUGFUs - (3GdQVj, GdYdhqj, GdMSjfj, GdehShj, CHh GdMSf, GdnqTpQja GdpqQVi, eMeO Hf GdMSjf Hf ehSi, J(B406(3g`s
(3ChdgG (B:s
(3cfJ MaX Gddg Ydjc Ojfc, hbhi aj GdYJQI GdWGgQI jbjfc SCdJfj Cf CUfa dc cJGHG jTJed Ydi NUGFU CNHGQ GdCFeI GdEKfi YTQ(B...s
(3BNQgG (B:s
(3hef cdGe dg Ydjg GdSdGe(B: (3ef MGSH faSg QHM(B... (3dh de jcf aj gPg GdabQ GdePchQI EdG gPg GdcdeI GdNjQI dcai(B... (3EP JTQaJ HcJGHI cJGH(B: (3NUGFU GdCFeI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B263s
(3GdCYdGe(B: (3L(B6(3, U(B99s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B263s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs